Reflections of the 1Malaysia Supply Chain (1MSC) - Munira, Halili; Latifah Naina, Mohamed; Fernando, Yudi (IGI Global USA, 2018)
This chapter focuses on the 1Malaysia Supply Chain framework that acts as the mover, which enables the whole 1Malaysia concept to be realized and implemented. It will highlight an in-depth review of the 1MSC. The 1MSC concept is derived from the integration between all the key players in the end-to-end supply chain process. This is where the stakeholders have the same goals in ensuring that the end to end process of supply chain is achieved. The 1MSC can be considered as an umbrella that governs the whole supply chain process. The driving force behind the realization of this concept is the strong foundation of its supply chain which integrates different parties as one. This article introduces the concept of National Development Incubator (NDI) where it combines the primary supply chain elements to achieve sustainable business and supply chain performance.